Measurement of respiratory sensation in patients referred for lung transplantation - Jastrzębski, Dariusz; Wyrwoł, Justyna; Ochman, Marek; Kowalski, Kamil; Lutogniewska, Wanda; Żegleń, Sławomir; Wojarski, Jacek; Kubicki, Piotr; Kozielski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The aim of the study was to evaluate dyspnoea sensation and its relation to clinical data and quality of life in patients referred for lung transplantation (LT). To measure respiratory sensation, the Medical Research Council questionnaire (MRC), Oxygen Cost Diagram (OCD), Baseline Dyspnoea Index (BDI) and Borg’s scale were used, whereas quality of life was evaluated with SF-36 and SGRQ. The study group consisted of 18 females and 68 males of average age of 52 ±10 years. 30 patients were diagnosed with idiopathic pulmonary fibrosis (IPF), 22 – COPD and 34 – other than IPF format form of idiopathic interstitial pneumonia other than IPF (IIP). The mean values for the clinical rating of breathlessness were in the upper limit in all clinical ratings of dyspnoea. In the reference group, there was a statistically significant correlation between dyspnoea and quality of life and physiologic measurements, especially 6 MWT (six-minute walking test). The correlation found between the level of dyspnoea and quality of life domains suggests that it would be worthwhile to add questions regarding dyspnoea to assess the severity of the disease, clinical symptoms and functional impairment when referring the patients for lung transplantation.